Lucretia Mott Speaks : The Essential Speeches and Sermons - Mott, Lucretia, 1793-1880 (Book collections on Project MUSE., 2017)
"Committed abolitionist, controversial Quaker minister, tireless pacifist, fiery crusader for women's rights--Lucretia Mott was one of the great reformers in America history. Her sixty years of sermons and speeches reached untold thousands of people. Yet Mott eschewed prepared lectures in favor of an extemporaneous speaking style inspired by the inner light at the core of her Quaker faith. It was left to stenographers, journalists, Friends, and colleagues to record her words for posterity. Drawing on widely scattered archives, newspaper accounts, and other sources, Lucretia Mott Speaks unearths the essential speeches and remarks from Mott's remarkable career. The editors have chosen selections representing important themes and events in her public life. Extensive annotations provide vibrant context and show Mott's engagement with allies and opponents. The speeches illuminate her passionate belief that her many causes were all intertwined. The result is an authoritative resource, one that enriches our understanding of Mott's views, rhetorical strategies, and still-powerful influence on American society." -- Publisher's description